Freshwater Fish Species of the Oorlogskloof River, Northern Cape Province, South Africa - Ramollo, P.P.; Schumann, M.; Pretorius, W.A.J. (Our Nature, 2013)
The freshwater fish of Oorlogskloof River were sampled in March 2010. The study aimed to determine the distribution and relative abundance of freshwater fish in the Oorlogskloof River. A total of 4643individuals represented by five fish species belonging to two families were sampled. The Barbus anoplus was only sampled in the upper reaches of the Oorlogskloof River gorge while endangered Labeobarbus capensis appeared downstream in the Oorlogskloof River. Barbus serra dominated the fish species in the system. The invasion of Tilapia sparmanni in this system was confirmed during the survey andthe species appeared to be widespread throughout the system. At this stage it does not appear to be posing a serious threat to the endangered fish species. The Oorlogskloof River can be considered as a potential refuge site for the conservation of some endemic and threatened freshwater fishes of South Africa. DOI: http://dx.doi.org/10.3126/on.v10i1.7746